Blood pressure percentile charts to identify high or low blood pressure in children. Issue 1 (December 2016) - Banker, Ashish; Bell, Cynthia; Gupta-Malhotra, Monesha; Samuels, Joshua
Abstract Background The goal was to develop familiar blood pressure (BP) charts representing BP percentile curves similar to CDC growth charts to improve screening of both high and low BP in children. Methods Since height accounts for substantially more BP variability than age and is a more direct measure of body size and maturation in children, height-specific BP percentile curves were drawn separately for males and females. We used the 2004Fourth Report data source and equations to calculate the BP threshold value for each gender and 5 cm height group. By slightly underestimating a child's BP percentile for high BP and slightly overestimating a child's BP percentile for low BP, these charts guarantee 100 % sensitivity in detecting abnormal BP. Sensitivity and specificity of the chart cut-offs were confirmed in a sample of 1254 healthy children from a school-based blood pressure screening program. Results The 1st, 5th, 25th, 50th, 75th, 90th, 95th, and 99th BP percentile curves are depicted in the chart for each corresponding gender and height from 85 to 190 cm, mimicking the ubiquitous CDC "growth charts". Shaded areas of the chart differentiate abnormal BP status categories: hypotension, normal BP, prehypertension, Stage 1 hypertension, and Stage 2 hypertension. Sensitivity was confirmed to be 100 % with specificity above 94 %. Conclusions These simplified BP charts improve upon currently available BP screening reference with the following features: (a) tracking BP longitudinally in an individual child, (b) full physiological range of BP percentiles represented in percentile curve format for rapid identification both high and low BP, (c) easy to use with absolute height alone avoiding the additional step of determining height percentile, (d) incorporation of adult threshold for pre-hypertension to assist in accurate transition from adolescence into adulthood, (e) high sensitivity and specificity to ensure all children at risk are identified with very few false positives.